The phytochemical and pharmacological profile of taraxasterol - Jiao, Fengjuan; Tan, Zengyue; Yu, Zhonghua; Zhou, Bojie; Meng, Lingyan; Shi, Xinyue (Frontiers in Pharmacology, 2022)
Taraxasterol is a major bioactive triterpenoid component of dandelion, a member of the family Asteraceae. Taraxasterol has been used for the prevention and treatment of various ailments such as liver damage, gastritis, colitis, arthritis, pneumonia, tumors, and immune system diseases. However, use of taraxasterol has been limited mainly to experimental studies. This review recapitulates previous work on taraxasterol and its potential for treatment and prevention of many diseases, highlighting its anti-inflammatory, anti-oxidative, and anti-carcinogenic properties, and its potential mechanisms of action. Finally, we suggest to analyze the probable inhibition of taraxasterol on abnormally activated glial cells in neurodegenerative diseases and the mechanism of taraxasterol on other cell biological processes in many diseases. We further recommend that extensive in vitro, in vivo, and clinical research focused on taraxasterol is required to further understand the physiological, pharmacological, and biochemical mechanisms underlying the effects of taraxasterol on diseases.